2002
DOI: 10.1046/j.1365-2230.2002.01163.x
|View full text |Cite
|
Sign up to set email alerts
|

Issues regarding nonattendance at a paediatric dermatology centre

Abstract: Nonattendance in paediatric dermatology clinics is a significant problem. We reviewed the charts of all 400 new referrals to the Prince of Wales Hospital (PWH) paediatric dermatology clinic in the year 2000. Sixty-six patients (17%) did not attend. The mean age +/- SD of attenders (7.5 +/- 5.1 years) and nonattenders (7.7 +/- 4.5 years) did not differ significantly. Forty-eight per cent of the referrals were females, 50% of the attenders were females and 67% of the nonattenders were male. Males were 2.1-fold m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 9 publications
2
25
0
Order By: Relevance
“…Non-attendance was associated with the waiting time for an appointment, as was observed in previous studies (12). Non-attendance varied between 13.0% and 30.8% according to the treating dermatologist.…”
Section: Discussionsupporting
confidence: 76%
“…Non-attendance was associated with the waiting time for an appointment, as was observed in previous studies (12). Non-attendance varied between 13.0% and 30.8% according to the treating dermatologist.…”
Section: Discussionsupporting
confidence: 76%
“…Other studies found NA rates in dermatology clinics ranging from 7.8 to 43.5% with rates from 17 to 27.6 being typical for clinics with a broad service provided to the general population. [4][5][6][7][8][9] Reasons for NA were prolonged waiting list, young age, gender and system errors. There is of course a major variation from one locality to another.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study of attendance at a specialist alcohol treatment centre in the UK 89 undertook multivariate analysis of patient characteristics of non-repliers (n = 100), non-attenders (n = 100) and attenders (n = 100) and found no statistically significant association between source of referral and attendance. A study in a paediatric dermatology clinic in Hong Kong 122 found that non-attendance was significantly higher among referrals from the emergency department than among referrals by private practitioners (p = 0.05).…”
Section: Patterns and Influences On Health-care Attendance Behaviourmentioning
confidence: 99%
“…Moore et al 126 investigated over 4000 appointments at a family practice centre in the USA and found that females tended to be less likely to miss appointments than males, although the effect was of borderline statistical significance in a multivariate analysis (OR 0.8, 95% CI 0.7 to 1.0; p = 0.06). Hon et al 122 report on a study of non-attendance at a paediatric dermatology clinic in Hong Kong and found that 67% of non-attenders were male and that males were more than twice as likely as females to fail to attend clinic (p = 0.010).…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation